2020
DOI: 10.1007/s10623-020-00803-1
|View full text |Cite
|
Sign up to set email alerts
|

Generalized isotopic shift construction for APN functions

Abstract: In this work we give several generalizations of the isotopic shift construction, introduced recently by Budaghyan et al. (IEEE Trans Inform Theory 66:5299–5309, 2020), when the initial function is a Gold function. In particular, we derive a general construction of APN functions which covers several unclassified APN functions for $$n=8$$ n = 8 and produces fifteen new APN functions for $$n=9$$ n = 9 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Unfortunately, despite a lot of efforts and some interesting recent advances (see, e.g., [20] and the references therein) on APN functions, studying the existence of APN permutations on 2 2m when m > 3 is a complicated wide-open problem. The existence of APN permutations operating on an even number of bits has been a long-standing open question until Dillon et al, who work for the NSA, provided an example on 6 bits in 2009.…”
Section: On Permutation Quadrinomials With Boomerang Uniformity and The Best-known Nonlinearitymentioning
confidence: 99%
“…Unfortunately, despite a lot of efforts and some interesting recent advances (see, e.g., [20] and the references therein) on APN functions, studying the existence of APN permutations on 2 2m when m > 3 is a complicated wide-open problem. The existence of APN permutations operating on an even number of bits has been a long-standing open question until Dillon et al, who work for the NSA, provided an example on 6 bits in 2009.…”
Section: On Permutation Quadrinomials With Boomerang Uniformity and The Best-known Nonlinearitymentioning
confidence: 99%
“…However, it turned out that this construction may be also used for construction of new (up to isotopic equivalence) planar functions [15]. Some generalisations of the isotopic shift constructions are proposed in [14]. In one of them an isotopic shift is applied to Gold-like functions which gives…”
Section: Overview On Known Constructions Of Apn and Ab Functionsmentioning
confidence: 99%
“…Many of the known APN functions are quadratic up to CCZ-equivalence, for instance the Gold functions x → x 2 i +1 for gcd(i, n) = 1 (see [30,32]), the two functions from F 2 10 and F 2 12 to itself defined in [27], and the classes defined in [5,6,11,12,13,14,15,16,18,22,40]. Indeed, to the best of our knowledge, at the time of writing only a single APN function is known which is not CCZ-equivalent to either a quadratic or a monomial function (see [28,8]).…”
Section: Quadratic Functionsmentioning
confidence: 99%
“…Note that in the recent works [11,12], the authors have found a new class of quadratic APN permutations which lead to new APN functions in dimension 8 and 9. In [11], it was shown that some of the APN functions from [28] can be classified into an infinite class.…”
Section: Known Apn Functions In Small Dimensionmentioning
confidence: 99%